Milk powder incorporation in the cereal-based Nepalese indigenous food bhakka and its quality assessment - Dahal S.; Bhattarai G.; Timsina P.; Rajbanshi B. K.; Dangal A.; Bohara A. (Acta Universitatis Sapientiae: Alimentaria, 2022)
This work aims to study the effect of milk powder incorporation on the nutritional and sensory quality of our traditional indigenous food, bhakka. Different samples were prepared replacing the rice flour by milk powder at different ratios (2.5:97.5, 5:95, 7.5:92.5, 10:90). Bhakka prepared from 100% rice flour was considered as control. Sensory-related results showed that 7.5% milk powder and 92.5% rice flour can be mixed to prepare an acceptable quality. The proximate analysis showed protein content of 5.18% in rice flour bhakka and 6.7% in milk-powder-incorporated bhakka. The milk-powder-incorporated bhakka had a fat content of 1.51%, crude fibre content of 0.18%, crude protein content of 6.70%, total ash content of 0.44%, and carbohydrate content of 62.3%, which was higher than that of rice flour bhakka. The product prepared can help in combating protein–energy malnutrition, adds a new taste as well as value to our traditional indigenous food.